How the COVID-19 pandemic has influenced pediatric rheumatology practice: Results of a global, cross-sectional, online survey - Batu, Ezgi Deniz (Semin Arthritis Rheum, 2020)
OBJECTIVES: The COVID-19 pandemic is a global health problem. We, as the EMERGE (EMErging RheumatoloGists and rEsearchers) group of PReS (Pediatric Rheumatology European Society) analyzed how the pandemic has affected pediatric rheumatology practice. METHODS: An online survey was developed to assess changes in pediatric rheumatology practice due to the pandemic. Results were analyzed using descriptive statistics. RESULTS: From 70 countries, 493 pediatric rheumatologists (80.3% in pediatric rheumatology practice for ≥5 years) responded to the survey. Around 70% disagreed that the pandemic led to reduced prescription of nonsteroidal anti-inflammatory drugs, conventional synthetic and biologic disease-modifying antirheumatic drugs. Almost half were more likely to taper corticosteroids faster. One-fifth hesitated to switch the major immunosuppressant during a flare. Patients encountering difficulties obtaining hydroxychloroquine and tocilizumab due to shortages were noted by 192 (38.9%) and 44 (8.9%), respectively. Twenty to 30% indicated that their patients had experienced a flare or delay in diagnosis/intervention due to postponed appointments.53% mentioned use of phone calls/smartphone applications while 47% shifted towards video consultations for patient care. Respondents indicated an increased number of patients with Kawasaki disease (30%), macrophage activation syndrome (15.6%), unusual vasculitic rashes (31.4%), and hyperinflammation (33.5%) during the pandemic. CONCLUSION: This is the largest survey to date addressing changes in pediatric rheumatology practice due to the COVID-19 pandemic. Primary changes were due to delays in clinic appointments, increase in use of virtual technologies, and concerns about the use of immunosuppressive therapies. An increased number of patients with Kawasaki disease/hyperinflammation mentioned by the respondents is noteworthy.